2018
DOI: 10.1002/jcb.26714
|View full text |Cite
|
Sign up to set email alerts
|

Hmox1 promotes osteogenic differentiation at the expense of reduced adipogenic differentiation induced by BMP9 in C3H10T1/2 cells

Abstract: Mesenchymal stem cells (MSCs) are multipotent progenitors that can differentiate into a variety of cell types under proper stimuli. Bone morphogenetic protein 9 (BMP9) is able to simultaneously induce both adipogenic and osteogenic differentiation of MSCs although the regulatory molecules involved remain to be fully identified and characterized. Heme oxygenase 1 (Hmox1) plays an essential role not only in fat metabolism, but also in bone development. In the present study, we investigated the functional role of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 64 publications
0
10
0
Order By: Relevance
“…HO1 possesses powerfully cytoprotective and antioxidant properties through the enzymatic degradation of heme (Consoli et al, 2021;Nitti et al, 2021). Some studies showed improve the osteogenic differentiation in mesenchymal stem cells (MSCs) line C3H10T1/2 and promote ectopic bone formation in nude mice (Liu et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HO1 possesses powerfully cytoprotective and antioxidant properties through the enzymatic degradation of heme (Consoli et al, 2021;Nitti et al, 2021). Some studies showed improve the osteogenic differentiation in mesenchymal stem cells (MSCs) line C3H10T1/2 and promote ectopic bone formation in nude mice (Liu et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Panax ginseng fruit extract (PGFE) induced the expression levels of Nrf2 and HO1, and recovered the osteoblast differentiation restrained by Porphyromonas gingivalis lipopolysaccharide (PG-LPS) in the human periodontal ligament cells, while tin protoporphyrin IX (SnPP), the inhibitor of HO1, suppressed the osteoblast differentiation ( Kim et al, 2020 ). Up-regulation of HO1 expression could improve the osteogenic differentiation in mesenchymal stem cells (MSCs) line C3H10T1/2 and promote ectopic bone formation in nude mice ( Liu et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Among these MSCs, EMSCs have the advantages of strong self-renewal ability, strong proliferation ability, multidirectional differentiation capacity, strong immunosuppressive effect, and convenient acquisition with large amounts ( Saleh et al, 2020 ). Notably, C3H10T1/2 cells, as mouse EMSCs, can differentiate into osteoblasts under the stimulation of various growth factors and active substances, which exhibit potential therapeutic value in bone tissue regeneration ( Lin et al, 2009 ; Liu et al, 2018 ; Jiang et al, 2019 ). Therefore, it is a key factor in effectively promoting the osteogenic differentiation of C3H10T1/2 cells in bone tissue engineering.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is necessary to understand the regulatory mechanisms behind the MSCs differentiation, which was regulated by BMP9 to improve the clinical application of BMP9. It has been reported that other cytokines combined with BMP9 can promote osteogenic differentiation of MSCs induced by BMP9, which will further optimize the bone-promoting effect of BMP9 [ 34 , 35 ]. Nevertheless, the exact biological molecular mechanism involved is still under investigation.…”
Section: Introductionmentioning
confidence: 99%